Assessment of the placement of aquatics activities in physical education - A. Albarracín; J.A. Moreno-Murcia (Asociación Española de Ciencias del Deporte, 2011)
The aim of the study has been to analyze the importance and consideration of the aquatic educational activities inside physical education on the part of the professorship in Secondary Education. The participants were 29 teachers of Secondary Education. There was in use a semistructured interview based on the following categories and subcategories: The professional path of the interviewed ones, the aquatic educational activities in the physical education, the reality in Murcia of the incorporation of aquatic activities in physical education (incorporation in the school area, advantages, difficulties, solutions) and the formation of the teacher in aquatic activities. The interview was beginning with questions on information sociodemográficos, developing with topics of reference as: "How much time you go as teacher of physical education?", "What opinion have you of the aquatic activities?", "What advantages and disadvantages do present the aquatic activities?", "Do you know the benefits of the exercise realized in the aquatic way?", between others. After the analysis of content, the physical, psychic and social benefits, as well as the formative ones and the kindness of the own way, have justified the good consideration that the teachers of physical education possess of the aquatic activities. New experimental studies are needed to confirm the kindness of the incorporation of the aquatic activities in the subject of physical education. Key Words:Aquatics activities, benefices, interview, teachers